2020
DOI: 10.1001/jamasurg.2019.5474
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Multimodal Prehabilitation vs Postoperative Rehabilitation on 30-Day Postoperative Complications for Frail Patients Undergoing Resection of Colorectal Cancer

Abstract: IMPORTANCE Research supports use of prehabilitation to optimize physical status before and after colorectal cancer resection, but its effect on postoperative complications remains unclear. Frail patients are a target for prehabilitation interventions owing to increased risk for poor postoperative outcomes.OBJECTIVE To assess the extent to which a prehabilitation program affects 30-day postoperative complications in frail patients undergoing colorectal cancer resection compared with postoperative rehabilitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
379
3
4

Year Published

2020
2020
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 341 publications
(452 citation statements)
references
References 51 publications
14
379
3
4
Order By: Relevance
“…Since then, several studies have investigated the clinical value of the CCI in CRC. Carli et al 35 used the CCI to measure 30day POCs as primary outcome to compare effects of multimodal prehabilitation with postoperative rehabilitation in frail patients undergoing CRC resection. Dumitra et al 36 explored the relationship of two POC-grading schemas (CDC and CCI) with postoperative quality of life after elective CRC surgery, and found there was a more consistent relationship between the CCI and postoperative health-related quality of life than CDC grades.…”
Section: Risk Factors For Overall Pocsmentioning
confidence: 99%
“…Since then, several studies have investigated the clinical value of the CCI in CRC. Carli et al 35 used the CCI to measure 30day POCs as primary outcome to compare effects of multimodal prehabilitation with postoperative rehabilitation in frail patients undergoing CRC resection. Dumitra et al 36 explored the relationship of two POC-grading schemas (CDC and CCI) with postoperative quality of life after elective CRC surgery, and found there was a more consistent relationship between the CCI and postoperative health-related quality of life than CDC grades.…”
Section: Risk Factors For Overall Pocsmentioning
confidence: 99%
“…Recently, some reviews showed that prehabilitation improved significantly functional capacity and self-reported physical activity but the impact on postoperative complications was limited [19]. Furthermore, a recent randomized trial has shown that a multimodal prehabilitation program did not affect postoperative outcomes in frail patients undergoing colorectal cancer resection [20]. Thus, even in a vulnerable population, the effects of prehabilitation and preoperative physical activity may be limited.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also specifically targeted frail older patients for prehabilitation. Carli et al showed that in frail patients undergoing colorectal cancer resection, multimodal prehabilitation involving exercise, nutritional, and psychological interventions did not improve 30-day postoperative outcomes [ 18 ]. Waite et al attempted a pilot home-based prehabilitation program directed at frail patients undergoing coronary artery bypass grafting (CABG) or valve surgery, showing the potential to improve functional ability and reduce in-hospital length of stay; results of the randomized trial are still pending [ 19 ].…”
Section: Discussionmentioning
confidence: 99%